Mathematical modeling of dissolved oxygen in fish ponds - W. J. S. Mwegoha; M. E. Kaseva; S. M. M. Sabai (Advances in Aquaculture and Fisheries Management, 2017)
A mathematical model was developed to predict the effects of wind speed, light, pH, Temperature, dissolved carbon dioxide and chemical oxygen demand (COD) on Dissolved Oxygen (DO) in fish ponds. The effects of organic feeds, aeration and fish activity were added to the model developed by Kayombo et al. for Waste Stabilization Ponds (Ecological Modelling 127(2000): 21 - 31) to reflect the situation in fish ponds. Model calibration and validation was done by use of average DO, pH, temperature, COD, CO2 and algae biomass data measured from RETCO fish ponds in Dar es Salaam; and light intensity data were adopted from Kayombo et al. (2000). Model results showed a linear relationship between simulated DO and measured DO in fish pond (r2 = 0. 87) for model calibration and (r2 = 0.88) for model validation. Simulation results also showed a general decrease of DO with time in 13 days by 28 and 38% for first and second batch, respectively. Thus, the model developed in this study could be used to predict the DO dynamics in fish ponds. Based on the model results, successful cultivation of healthy fish may require that retention time for water in the fish pond be 10 days.